2009
DOI: 10.3354/meps08223
|View full text |Cite
|
Sign up to set email alerts
|

Seabird nestling diets reflect latitudinal temperature-dependent variation in availability of key zooplankton prey populations

Abstract: We report on historical (1978 to 1982) and more recent (1996 to 2000) variation in the nestling diet of Cassin's auklet Ptychoramphus aleuticus breeding at Triangle Island (southern) and Frederick Island (northern), British Columbia, Canada; these islands are influenced by the California and the Alaska Current ecosystems, respectively. Ocean climate conditions off the British Columbia coast varied tremendously between 1978 and 2000. At both colonies, the nestling diet was composed largely of copepods and euph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Research on seabird nestling diet is consistent with the concept that the phenology of temperature-dependent copepod prey and Cassin's Auklet predator populations can be mismatched on Triangle Island in the California Current Ecosystem but a similar mismatch has not been observed on Frederick Island, in the Gulf of Alaska Ecosystem (Bertram et al 2009). In addition, local adult annual survival for Cassin's Auklet is lower on Triangle Island, where the population has declined significantly (1989-2009, Rodway and Lemon 2011), than on Frederick Island (Bertram et al 2005) where declines have not been reported.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…Research on seabird nestling diet is consistent with the concept that the phenology of temperature-dependent copepod prey and Cassin's Auklet predator populations can be mismatched on Triangle Island in the California Current Ecosystem but a similar mismatch has not been observed on Frederick Island, in the Gulf of Alaska Ecosystem (Bertram et al 2009). In addition, local adult annual survival for Cassin's Auklet is lower on Triangle Island, where the population has declined significantly (1989-2009, Rodway and Lemon 2011), than on Frederick Island (Bertram et al 2005) where declines have not been reported.…”
supporting
confidence: 67%
“…as an index for the timing for N. cristatus in response to interannual variation in SST near the seabird colonies. Note that N. cristatus represented > 99% of the copepod biomass in the nestling diet of Cassin's Auklet on Triangle and Frederick islands during the time frame of this study (Bertram et al 2009). Note, too, that Batten and Mackas (2009) demonstrated a shortened duration of the annual N. plumchrus biomass peak in the Northeast Pacific in response to ocean climate warming, in addition to earlier peak biomass timing.…”
Section: Estimation Of Peak Timing Of Zooplankton Preymentioning
confidence: 71%
See 2 more Smart Citations
“…In 2005, an unusual atmospheric blocking event severely delayed spring transition winds and hence marine production in the California Current Ecosystem [ 37 ]. Colonial seabirds off the West Coast of Washington [ 38 ] and Vancouver Island [ 39 , 40 ] failed to breed in those two years. Thus, concurrent movements of marbled murrelets away from marine areas that lack prey could explain the interannual variation in radar counts.…”
Section: Discussionmentioning
confidence: 99%